CULTURAL AND MORAL HERITAGE OF CATHOLICISM IN BRIDESHEAD REVISITED - Ladislava Ivancova (European Scientific Journal, ESJ, 2014)
This article analyses the historical novel by an English novelist,Evelyn Waugh, Brideshead Revisited. Introduction to the novel provides abrief account of circumstances behind Waugh´s motivation to write the noveland its criticism. The author analyses the conversion of the main character inthe novel, Charles Ryder, to the Catholic faith. The re/conversion of anothercharacter, Julia, to the Old Faith is discussed and analysed further in thearticle. Through comparison of codes of behaviour of other characters fromthe novel, the author presents two miscellaneous characters of people. Theauthor states that the difference between these people stems from theirdifferent approach towards the values that represent the Roman Catholicism,which formed the character of people in the past. The author focuses on theinfluence of religion accepted in childhood on the adult life of an individual.The paper also contains analyses of characters that represent the modern ageera following the World War II. The analysis puts these characters,agnostics, in a sharp contrast with the Anglo-Catholics. The Marchmainsrepresent the people of the past, who lean on their family traditions thatoriginate from their long preserved history and Catholic culture.